Sectional and Ricci Curvature for Three-Dimensional Lie Groups - Gerard Thompson; Giriraj Bhattarai (Journal of Mathematics)
Formulas for the Riemann and Ricci curvature tensors of an invariant metric on a Lie group are determined. The results are applied to a systematic study of the curvature properties of invariant metrics on three-dimensional Lie groups. In each case the metric is reduced by using the automorphism group of the associated Lie algebra. In particular, the maximum and minimum values of the sectional curvature function are determined.